Peranan Serasah Terhadap Sumbangan N dan P pada Agroekosistem Kopi - EVIZAL, RUSDI; TOHARI, TOHARI; PRIJAMBADA, IRFAN D.; WIDADA, JAKA (Agrotrop : Journal on Agriculture Science; Vol 2 No 2 (2012), 2014)
Litter is the main source of organic matter and nutrient entrance in shade grown coffee agroecosystems. Shade trees provide ecological and economic benefits in coffee agro-ecosystems that indicate the key factor for sustainable coffee production. This study examined the role of litter on nutrient (N and P) returning in coffee agro-ecosystems. The experimental plots of Coffea canephora were constucted at benchmark site of Conservation and Sustainable Management of Below-Ground Biodiversity (CSM-BGBD), in Sumberjaya Subdistrict, West Lampung, Indonesia, during 2007-2010. Types of shade trees to be examined were legume shade trees of Gliricidae sepium and Erythrina sububrams, non-legume tree of Michelia champaca, and no shade tree. The results showed that: (1) kind of shading determined litter productivity of coffee agro-ecosystems. Litter productivity of coffee agro-ecosystems with shade trees increased coffee bean yield, (2) litter was an important source of N and P that returned into the soil. Amount of nitrogen from litter biomass has linier effect on coffee bean yield.
Keywords: coffee, legume trees, yield